Employability Model Reviewed from Career Planning, Self-Adjustment, and Need for Achievement - Alya Surya Diningrum; Fatwa Tentama (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
Vocational High Schools play a crucial role in preparing graduates to enter the workforce. However, many Vocational High School graduates continue to face challenges in achieving optimal work readiness. These issues highlight the need for further research to identify the factors that influence students’ employability. This study aims to test a theoretical model examining the influence of career planning, self-adjustment, and need for achievement on the employability of Vocational High School students. The research employs a quantitative approach, utilizing Structural Equation Modeling (SEM) for data analysis. The participants comprised 360 Grade XII students from Vocational High School